Guillain Barré Syndrome in the First Trimester of Pregnancy after Tetanus Toxoid Immunization: A Rare Case Report and Review of Literature - Kumar, Dinesh; Goyal, Manu; Sani, Umme A.; Singh, Pratibha (Journal of Fetal Medicine, 2024)
Guillain Barré syndrome (GBS) is a rare neurological entity that presents as rapidly progressive symmetrical ascending demyelinating polyneuropathy. Its incidence is infrequent during pregnancy at 1.2 to 1.9 cases per 100,000 population. It is associated with very high maternal mortality and pregnancy complications. Its management during pregnancy is challenging as delay in diagnosis occurs due to rarity and overlapping symptoms. We report a case of a 23 year old primigravida who presented at 3 months of gestation with rapidly progressive lower limb paralysis after tetanus toxoid immunization. She was managed by a multidisciplinary team with intensive care admission, ventilator support, and intravenous immunoglobulins. She showed improvement after 4 weeks and was discharged in a stable condition with little residual weakness in her lower limbs. On follow up, she achieved full recovery. The outcome of the pregnancy was vaginal birth of a male child with no postpartum relapse. GBS is a rare entity during pregnancy and has a high maternal mortality rate. Hence, it is important to have a strong clinical suspicion and aggressive treatment for favorable maternal and fetal outcomes.
Keywords: GBS; pregnancy; tetanus toxoid